2020
DOI: 10.19101/ijatee.2019.650068
|View full text |Cite
|
Sign up to set email alerts
|

A review of augmented reality in educational applications

Abstract: In education, augmented reality (AR) provides a better user experience due to its features of displaying 3D virtual information and interaction. Thus, many scholars have been attracted to developing this technology in their research. However, there are different types of AR technology represented in the educational environment. Therefore, the impact of using this technology in research may differ from one type to another. This paper provides an overview of AR technology in the educational environment. It inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…As conclusion, AR showed a great potential and benefits in the education sector [9]. It can be designed to stimulate any academic scenario.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…As conclusion, AR showed a great potential and benefits in the education sector [9]. It can be designed to stimulate any academic scenario.…”
Section: Discussionmentioning
confidence: 77%
“…Technology-Enhanced Learning (TEL) research has increasingly focused on emergent technologies such as Augmented Reality (AR) [3]. A considerable amount of literature has been published in using AR in educational contexts [4][5][6][7][8][9][10] due to the ability of AR to provide extra digital content for any subject that has some difficulties in understanding [52,90,94]. For example, Zainab and Huda [9] showed that -user satisfaction‖ is the most frequently mentioned positive impact of using AR in education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented reality technology encourages students to be self-learner, fosters a desire to explore new possibilities, and replaces costly laboratory equipment with multimedia models (Majeed & Ali, 2020 ; Noroozi et al, 2019 ; Singh et al, 2019 ; Wang et al, 2018 ). It creates an engaging environment by overlaying contextual information on real objects and further enhances their visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yuen et al [ 23 ], educational AR-applications can be designed for discovery-based learning (DBL), object modelling (OM), game-based learning (GBL), for the teaching of specific skills in training, or they can be integrated into distinct educational AR-books, with GBL and OM being the most frequently addressed purposes of educational AR-applications [ 24 ]. AR in education can help learners to conduct authentic explorations in the real world by displaying virtual elements [ 25 ], and can facilitate the observation of processes that cannot be perceived with the naked eye [ 26 ].…”
Section: Introductionmentioning
confidence: 99%